COMPOSITION AND POTENCY OF YOUNG COCONUT WATER FOR HEALTH (COCOS NUCIFERA L.): A SYSTEMATIC REVIEW - Nadila, Elva; Azzahro, Fatimah; Hasanah, Fifi Yulisa; Proverawati, Atikah (International Journal of Biomedical Nursing Review, 2022)
Introduction: Young coconut water (Cocos nucifera L.) is a liquid produced by the endosperm of coconut fruit that has clear color and sweet taste. Young coconut water is rich in nutrients that have the potential for the health of the human body, such as potassium, sodium, and calcium content. Apart from these ingredients, there are several ingredients found in the results of other studies. Purpose: The purpose of this systematic review was to identify and discuss the potential content of young coconut water for health. Methods: The method used is a literature study from related articles obtained from the electronic database Science Direct and Google Scholar. Results: The results of the 7 selected articles indicate that young coconut water contains vitamins, sugars, amino acids, and minerals. Discussion: These contents play a role in hematopoiesis, thereby preventing anemia. The content of vitamin C can fight free radicals and prevent urolithiasis in the kidneys. Glucose content can balance blood sugar levels. The content of amino acids in the form of L-arginine plays a role in the body's antioxidant system. Its mineral content which resembles body fluids is able to maintain the body's osmotic pressure. Conclusion: So, it can be concluded that young coconut water has a lot of potential for health.